The Connection between the Toxicity of Anthracyclines and Their Ability to Modulate the P-Glycoprotein-Mediated Transport in A549, HepG2, and MCF-7 Cells - Aneta Rogalska; Marzena Szwed; Błażej Rychlik (The Scientific World Journal)
Multidrug resistance (MDR) is a major obstacle to the successful chemotherapy of solid tumors. We compared the resistance of the most popular solid tumors, breast adenocarcinoma (MCF-7 cell line) and nonsmall cell lung (A549 cell line) hepatocellular liver carcinoma (HepG2 cells), to aclarubicin (ACL) and doxorubicin (DOX). This research aimed at determining the relation between the toxicity of ACL and DOX, their cell accumulation, and then effect on P-glycoprotein functionality. ACL is more cytotoxic for tumor cells compared to DOX. The intracellular concentration of drugs in cancer cells was dependent on the dose of the drugs and the time of incubation. The P-gp inhibitor Verapamil (V) increased DOX accumulation in all tested cell lines. By contrast, the intracellular level of ACL was not affected by this modifying agent. The assessment of the uptake of 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazolocarbocyanine iodide (JC-1) or Rhodamine 123 (R123) allows the evaluation of the different influence of drugs on P-gp activity which is in agreement with the estimation of expression measured by MDR-1 shift assay. These data suggest that ACL is less P-gp dependent than DOX and consequently may be used in a clinical setting to increase treatment efficacy in resistant human tumors.